Práticas de Discussão em Sala de Aula de Matemática: os casos de dois professores - Rodrigues, Cátia (2018)
Mathematical discussions are a powerful activity for students’ learning by supporting the presentation, justification, argumentation, and systematization of the reasoning associated to the work on mathematical tasks. The teacher plays a fundamental role in leading the discussion, being called to carry out a set of instructional actions, based on his/her didactic knowledge. In this paper, we present discussions practices of two 8 th grade mathematics teachers, in order to understand how they use discussions when teaching algebra topics. The study is qualitative and interpretive and is based on the case study of two teachers, who are part of a collaborative group. The results show that the teachers structure the mathematical discussion at three main moments and manage the discourse for the generalization of algebraic ideas. Thereby, they undertake a set of instructional actions that help the presentation, justification, and argumentation of several solution strategies.